The Implementation of the Amtsilati Method in Teaching Classical Islamic Texts at Madrasah Tsanawiyah Islamiyah Zainul Hasan Genggong - Moh. Hazin Ubaidillah Abd Salam; Ahmad Zainullah; Ainur Rofiq Sofa (Universitas Al-Amien Prenduan, 2026)
This study aims to describe the implementation of the Amtsilati method in teaching classical Islamic texts to students of Madrasah Tsanawiyah Islamiyah Zainul Hasan Genggong and to analyze its effectiveness in improving students’ ability to understand Arabic classical texts, particularly in grammatical and morphological aspects which are fundamental for comprehending traditional Islamic literature. The significance of this study lies in the need to develop effective teaching methods that facilitate the learning of classical texts, as students often encounter difficulties in understanding them due to the complexity of their linguistic structures and limited mastery of Arabic grammar. This research employed a qualitative descriptive method. Data were collected through direct observation, interviews with teachers and students, and documentation analysis related to the implementation of the method. The findings revealed that the implementation of the Amtsilati method significantly contributed to improving students’ comprehension of classical texts and enhancing their ability to analyze linguistic structures and identify grammatical and morphological rules practically. The results also indicated that this method increased students’ motivation to study classical texts because of its gradual presentation of materials and intensive practical exercises that strengthen understanding. The study concludes that the Amtsilati method is an effective instructional approach for teaching classical Islamic texts due to its systematic framework that integrates theoretical and practical aspects. This method plays an important role in facilitating Arabic language learning and improving students’ understanding of classical texts at the junior secondary Islamic school level. Keywords: Amtsilati method, teaching classical islamic texts, text comprehension, arabic language learning, islamic junior secondary school.